Free Sex Behavior in College Students Reviewed from Pathophysiological Mechanisms in HIV Patients: Scoping Review - Permana, Dicka Trie; Yusuf, Muhamad; Khairunnisa, Musyrifah; Aghista, Rizka Dwi Putri; Nurcholisa, Siti; Putri, Sofi Amelia; Khoirunnisa, Syifa; Fransisca, Talia Berliana; Aisar, Tasya Rahadatul; Rifqi, Tiara; Sopiah, Popi (Sarana Ilmu Indonesia (salnesia), 2025)
HIV/AIDS remains a major health concern among adolescents, with promiscuous sexual behavior identified as a key factor contributing to the rising number of cases. This study aims to examine the correlation between promiscuous sexual behavior and HIV transmission through a review of various scientific sources. A scoping review method was used, as it allows for broad and systematic mapping of the literature particularly on complex topics that have not been extensively studied. Articles were obtained from the Google Scholar, PubMed, and ScienceDirect databases, with publication years ranging from 2019 to 2025. The keywords used included “Pathophysiology,” “HIV,” “Free Sex,” and “Student.” A total of eight relevant articles were selected for analysis. The results showed that unprotected casual sex is the primary cause of HIV transmission, especially among university students. A lack of understanding about HIV and its modes of transmission contributes to high infection rates. In addition, students infected with HIV face significant psychosocial impacts. Therefore, education about the risks of promiscuous sexual behavior and the provision of psychosocial support are essential to reducing stigma and improving quality of life. Further research is needed to enhance understanding of the mechanisms of HIV transmission through risky sexual behavior.